State fragility and economic vulnerability: What is measured and why? - Patrick Guillaumont; Sylviane Guillaumont Jeanneney (Fondation pour les études et recherches sur le développement international (FERDI), 2009)
State fragility is a concept that emerged among the international community of donors in order to adapt aid policies to particularly difficult situations. Fragility has thus been measured to design a special treatment in favour of fragile states, otherwise lef t behind. In this context, but somewhat paradoxically, fragility has been measured by a low policy and institutional assessment, operated through the "CPIA", in the multilateral development banks that also used/use this index as the major indicator to determine their aid allocation. Some other more multi-dimensional measures have broadened the scope of the indicators used to identify fragility. All these measures appear to be rather subjective, unstable, leading to discordant lists of fragile states, and not really representing a risk of failure. For analytical and operational reasons, there may be advantages in turning to the concept of structural economic vulnerability (apparently close, but very different). Structural economic vulnerability, the risk to be durably affected by exogenous shocks, depends both on the size of the shocks and on the exposure to the shocks. It can be measured by the Economic Vulnerability Index (EVI), set up at the UN to identify the Least Developed Countries (LDCs). It is a rather objective and stable index, also reflecting a risk of becoming a fragile state, as illustrated by the fact that most of the LDCs have been considered as fragileat least once. Such an index can be used as a positive criterion of aid allocation, beside the CPIA, a low income per capita and a low level of human capital. Its inclusion among aid allocation criteria is supported by equity, effectiveness and transparency reasons. It allows one to treat the case of fragile states in an integrated framework, leaving only the most acute cases of fragility or failure for exceptional treatment.Document disponible comme Document de travail du Rapport européen sur le développement
Keywords: 330